Law and the Quest for Gender Equality - Thornton, Margaret (Global Thinkers Series, 2023)
For centuries, law was used to subordinate women and exclude them from the public sphere, so it cannot be expected to become a source of equality instantaneously or without resistance from benchmark men-that is, those who are white, heterosexual, able-bodied and middle class. Equality, furthermore, was attainable only in the public sphere, whereas the private sphere was marked as a site of inequality; a wife, children and servants could never be the equals of the master. Despite their ambivalence about the role of law and its contradictions, women and Others felt that they had no alternative but to look to it as a means of liberation. This skewed patriarchal heritage, the subtext of this collection of essays, has continued to impede the quest for equality by women and Others. It informs not only gender relations in the private sphere, as illustrated by domestic violence and sexual assault, but also the status of women in the public sphere. Despite the fact that women have entered the paid workforce-including the professions-in large numbers, they are still expected to assume responsibility for the preponderance of society's caring. The essays show how maternal and caring roles, which are still largely viewed as belonging to an unregulated private sphere, continue to be invoked to detract from the authority of the feminine in the public sphere. The promise of antidiscrimination legislation in overcoming the heritage of the past is also shown to be somewhat hollow.